PERSEPSI BAURAN PEMASARAN KONSUMEN LAYANAN POS EXPRESS DI KANTOR POS JEMBER 68100 - Azis, Wachyudi; Sularso, R. Andi (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2014)
Thepurpose of this study is to analyze and prove the perception of the marketing mix can influence the decision to buy the product in the Express Post service Post Office Jember. The number of informants as many as 115 people, consisting of career women, employees of private, academic graduates and housewives. The total sample of 10 informants as respondents drawn using sampling techniques purpusive. The results of the study explained that there is a positive perception raises a significant effect on the incidence of satisfaction and purchase decisions improve service revenue performance products Pos Express. This is indicated by the results of the interview datavaliditycan be tested. Keywords: Perception ofProduct, Price, Promotion, Place, Process, Personnel, Physical evidence (Perception Marketing Mix).